A two‐level approach to the problem of rail freight car fleet composition - Bojovic, Nebojsa; Boskovic, Branislav; Milenkovic, Milos; Sunjic, Aleksandar (Transport, 2010)
One of the main objectives for a rail company is to minimize the size of rail freight car fleet in order to reduce operating costs. The problem of rail freight car fleet composition is aimed at determining an optimal structure and size of freight car fleet in order to respond to actual transport demand. A rail company must have capabilities to respond to actual transport demand in case it wants to increase the level of competitiveness on the transport market. Therefore, it is necessary that the structure and size of rail freight car fleet correspond to the structure and size of rail transport demand. In this paper, we developed a two‐level approach to determining an optimal rail freight car fleet composition. This approach has been tested for the case of the Public Enterprise ‘Serbian Railways’ and the obtained results show the potential for a practical application of the proposed approach.First published online: 27 oct 2010